YASMIN The Scientist - Faruqi, Saadia; Aly, Hatem (North Mankato, Minnesota : Picture Window Books, 2021)
Everyone seems to have an idea for the science fair except for Yasmin, but after some failed experiments Yasmin's snack break with Nani inspires an idea.
Keywords: Yasmin (Fictitious character) -- Juvenile fiction; Science fairs -- Juvenile fiction; Schools -- Juvenile fiction; Pakistani Americans -- Juvenile fiction; Muslims -- United States -- Juvenile fiction